Decision to incision interval for emergency caesarean section and postoperative outcomes in a resource limited rural Kenyan public hospital - Kamotho, David; Pertet, Anne M.; Ogwayo, Isaac (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Standard guidelines recommend that delivery by caesarean section should be ideally initiated within 30 minutes of the decision to operate to avoid maternal and foetal compromise in labour. The purpose of this study was to investigate the extent to which these guidelines can be achieved in limited resource hospital. Methods: Authors used a secondary data from 330 patient’s files of women who had a caesarean section from December 2013 retrospectively to January 2012. Results: The main indications for caesarean section was obstructed labour (18.5%) for mothers and foetal distress (6.4%). Though 74% of the mothers gave consent to be operated within the 30-minute guideline, only 3% were prepared for operation within this period. Only 24% of the caesarean sections were conducted within one hour after the decision was made for the operation. About 38% of the women, and 30% of the babies developed complications after the caesarean section. Haemorrhage was the leading complication in mothers while the main complication for babies was babies with an Apgar score of 5 and below. Conclusions: The 30- minute recommended guideline for caesarean section was not achieved, and there was evidence of adverse post-operative outcome as a result of not meeting the global standards.